Ultrasound-assisted enzymatic extraction of Corni Fructus alpha-glucosidase inhibitors improves insulin resistance in HepG2 cells. Issue 20 (25th August 2021) - Han, Binkai; Sun, Haoqiang; Yang, Xiaolin; Wang, Ting; He, Changfen; Zhao, Ke; An, Shujing; Guo, Chen; Niu, Dou; Xue, Xiaochang; Kang, Jiefang
Abstract : Alpha-glucosidase inhibitors from Corni Fructus were optimized by ultrasound-assisted enzymatic extraction using response surface methodology and actively improved disordered glucose metabolism. Abstract : Corni Fructus (CF) is a traditional medicine and beneficial food with multifaceted protective effects against diabetes and its complications. Since alpha-glucosidase inhibitors (GIs) are promising first-choice oral antihyperglycemic drugs for diabetes, we examined whether GIs from CF (GICF) are useful for diabetes treatment. Therefore, GICF was extracted by ultrasound-assisted enzymatic extraction (UAEE) that is optimized by a three-level, four-factor Box–Behnken design and determined by ultra-performance liquid chromatography. Compared to 36.31 mg g −1 without enzyme treatment, the GICF yield increased to 70.44 mg g −1 via UAEE under optimum conditions (0.5% compound enzyme extracted in 23 min at 46 °C and pH 4.8). The activity (91.99%) of GICF was as predicted (93.28%). When GICF was used in an insulin-resistant HepG2 cell model, it significantly ameliorated the glucose metabolism in a dose-dependent manner. Our findings indicate that UAEE may be an innovative method for functional food extraction and a potential strategy for high-quality food ingredient (such as GI) production with high efficiency and productivity.